Wearable Smart Contact Lenses for Continual Glucose Monitoring: A Review - Elsherif, Mohamed; Moreddu, Rosalia; Alam, Fahad; Salih, Ahmed E.; Ahmed, Israr; Butt, Haider (Frontiers in Medicine, 2022)
Diabetes mellitus is a chronic disease requiring a carefully management to prevent its collateral complications, such as cardiovascular and Alzheimer diseases, retinopathy, nephropathy, foot and hearing impairment, and neuropathy. Self-monitoring of blood glucose at point-of-care settings is an established practice for diabetic patients. However, current technologies for glucose monitoring are invasive, costly, and only provide single snapshots for a widely varying parameter. On the other hand, tears are a source of physiological information that mirror the health state of an individual by expressing different concentrations of metabolites, enzymes, vitamins, salts, and proteins. Therefore, the eyes may be exploited as a sensing site with substantial diagnostic potential. Contact lens sensors represent a viable route for targeting minimally-invasive monitoring of disease onset and progression. Particularly, glucose concentration in tears may be used as a surrogate to estimate blood glucose levels. Extensive research efforts recently have been devoted to develop smart contact lenses for continual glucose detection. The latest advances in the field are reviewed herein. Sensing technologies are described, compared, and the associated challenges are critically discussed.